Perinatal palliative care: Parent perceptions of caring in interactions surrounding counseling for risk of delivering an extremely premature infant. Issue 2 (4th November 2013) - Kavanaugh, Karen; Roscigno, Cecelia I.; Swanson, Kristen M.; Savage, Teresa A.; Kimura, Robert E.; Kilpatrick, Sarah J.
Abstract: Objective: When infants are at risk of being born at a very premature gestation (22–25 weeks), parents face important life-support decisions because of the high mortality for such infants. Concurrently, providers are challenged with providing parents a supportive environment within which to make these decisions. Practice guidelines for medical care of these infants and the principles of perinatal palliative care for families can be resources for providers, but there is limited research to bridge these medical and humanistic approaches to infant and family care. The purpose of this article is to describe how parents at risk of delivering their infant prior to 26 weeks gestation interpreted the quality of their interpersonal interactions with healthcare providers. Methods: Directed content analysis was employed to perform secondary analysis of data from 54 parents (40 mothers and 14 fathers) from the previously coded theme "Quality of Interactions." These categorized data described parents' encounters, expectations, and experiences of interactions that occurred prenatally with care providers. For this analysis, Swanson's theory of caring was selected to guide analysis and to delineate parents' descriptions of caring and uncaring interactions. Results: Parents' expectations for caring included: (a) respecting parents and believing in their capacity to make the best decisions for their family (maintaining belief); (b) understanding parents' experiences and their continued need to protect their infant (knowing); (c) physically and emotionally engaging with the parents (being with); (d) providing unbiased information describing all possibilities (enabling); and (e) helping parents navigate the system and creating a therapeutic environment for them in which to make decisions (doing for). Significance of Results: Understanding parents' prenatal caring expectations through Swanson's theory gives deeper insights, aligning their expectations with the palliative care movement.